TI_GERICHTE 52.2020.550 vom 1. Februar 2021 , Commesse pubbliche. Bando di concorso. Criterio di idoneità insostenibile - TI Tribunale d'appello (2021)
Commesse pubbliche. Bando di concorso. Criterio di idoneità insostenibile